Tailoring and Boosting the Features of ZnO/GO Nanoparticles Doped PVA/PEG Polymer Blend for Optoelectronics Applications - Jasim, Saad Abbas; Al Maimuri, Najah M. L.; Hashim, Ahmed; Abbas, Mohammed H.; Hadi, Aseel (Trends in Sciences, 2025)
The goal of the present study is to fabricate PVA/PEG/ZnO-GO nanocomposites and investigate their optical features. The PVA/PEG/ZnO-GO nanocomposites have been prepared by utilizing casting technique with various concentrations of (ZnO-GO) nanoparticles. The optical features have been investigated at a range of wavelengths from (220 - 820 nm). The analysis reveal that when (ZnO-GO) nanoparticles ratio has been increased, absorption value of PVA/PEG was boosted whereas the transmittance value was drop down. Whenever (ZnO-GO) nanocomposites ratio have been rise, the band gap was reduced from 4.7 to 3.9 eV for allowed transition from 4.3 to 3.2 eV for forbidden transition. The reduce of energy gap making PVA/PEG/ZnO-GO nanocomposites are suitable for many optoelectronics applications like sensors, diodes, solar cell, transistors and photovoltaic cell. The other optical features of PVA/PEG/ZnO-GO nanocomposites have been boosted. Finally, the outcomes of optical features reveal that the PVA/PEG/ZnO-GO nanocomposites are being possible to be utilized in many optoelectronics applications. HIGHLIGHTS Synthesis of PVA/PEG/ZnO-GO quaternary nanocomposites Investigating the effect of ZnO-GO nanocomposites on optical properties of PVA/PEG The energy gap of PVA/PEG blend decreased from 4.7 to 3.9 eV for allowed transition & from 4.3 to 3.2 eV for forbidden transition. The optical properties showed the PVA/PEG/ZnO-GO nanocomposites can be useful in different optical devices. GRAPHICAL ABSTRACT